Surveillance for arboviruses and leptospirosis among non-malarial acute febrile illness outpatients in areas affected by Cyclones Idai and Kenneth in Mozambique - Mugabe, Vánio André; Inlamea, Osvaldo Frederico; Ali, Sádia; Maholela, Plácida; Melchior, Bibiana; Muianga, Argentina Felisbela; Oludele, John; Sumail, Andarusse; António, Virgílio; Monteiro, Vanessa Onofre; Chongo, Inocêncio; Kitron, Uriel; et al. (Frontiers in Tropical Diseases, 2023)
The floods associated with the landfall of cyclones Idai and Kenneth in Mozambique between March and April 2019 had a major impact on the country’s public health and placed the affected population at risk for vector- and rodent-borne diseases. Aiming to improve the diagnostic capacity, yield information to guide public health responses, and assess potential short-term effects of cyclones Idai and Kenneth on arboviruses (dengue, Zika, and chikungunya) and leptospirosis, a clinical and laboratory surveillance for non-malarial acute febrile illness was established in six health units located in different districts within the two provinces (Sofala and Cabo Delgado) affected by the cyclones. Patients were tested using real-time reverse transcriptase polymerase chain reaction (qRT-PCR) for dengue (DENV), Zika (ZIKV), and chikungunya (CHIKV) viruses and using enzyme linked immunoassays (ELISA) to detect nonstructural DENV protein 1 (NS1), as well as DENV, ZIKV, CHIKV, and Leptospira IgM antibodies. From April to September 2019, 305 patients aged ≥15 years were enrolled, of which 58.4% were women and the median age was 30 years old. All patients were qRT-PCR negative for the targeted arboviruses, but three (1.0%) were positive for DENV NS1 ELISA. Specific IgM antibodies against DENV, ZIKV, CHIKV or Leptospira were found in the serum of 104 (34.1%) patients. Our results indicate that vector- and rodent-borne disease transmission occurred in all districts under investigation in the wake of cyclones Idai and Kenneth, including some regions where cases had not been previously detected. The investigation provided useful information for post-cyclone emergency response purposes.